Collaborative product assembly design and assembly planning : methodologies and applications - Lu, Cong, 1971-; Fuh, J. Y. H.; Wong, Y. S. (Yoke-San) (Oxford ; Philadelphia, PA : Woodhead Pub., 2011)
Collaborative product assembly design and assembly planning presents several newly-developed methodologies and applications for collaborative assembly design and assembly planning, two important steps during the product development life cycle. These benefits include effective and rapid assembly design and assembly planning, thereby reducing the development cost and helping manufacturers enhance profit. With increased development in computer technologies and the Internet, the traditional assembly design and assembly planning have evolved around collaborative assembly design and assembly planning to speed up the product development process. Research in this area has attracted much attention in the past decade. Based on research work in the past few years, this book will present several newly-developed methodologies and applications for collaborative assembly design and assembly planning to improve the efficiency of product development in a collaborative design environment. Provides practical and realistic solutions to engineering problemsMethodologies introduced will lead to future commercialisation of systemsDetailed step-by-step case study examples will illustrate the methodologies and be discussed thoroughly.
6.1 The design problems identified from the assembly planning results6.2 The overall redesign guidelines from the assembly planning results; 6.3 Summary; Reference; 7 Collaborative assembly planning; 7.1 System framework and working mechanism; 7.2 The workflow of collaborative assembly planning; 7.3 Case study; 7.4 Summary; References; 8 Conclusions and recommendations; 8.1 Conclusions; 8.2 Recommendations for future works; Index.
Includes bibliographical references and index.
Keywords: Assembly-line methods; Industrial design; TECHNOLOGY & ENGINEERING -- Industrial Engineering; TECHNOLOGY & ENGINEERING -- Industrial Technology; TECHNOLOGY & ENGINEERING -- Manufacturing; TECHNOLOGY & ENGINEERING -- Technical & Manufacturing Industries & Trades; Assembly-line methods; Industrial design